The impact of the surface on step-bunching and diffusion of Ga on GaAs (001) in metal-organic vapour phase epitaxy. (18th July 2016) - Pristovsek, Markus; Poser, Florian; Richter, Wolfgang
Abstract: We studied diffusion by measuring step-bunching, island spacing, and the transition from step-flow growth to two-dimensional island growth of (001) GaAs in metal-organic vapour phase epitaxy and correlated them with the surface reconstruction measured by reflectance anisotropy spectroscopy. The V/III ratio had a small effect, while the square root of the growth rate was anti-proportional to the diffusion length. The thermal activation energy was about 2.3 eV on c ( 4 × 4 ) terraces and 1.6 eV on ( 2 × 4 ) domains at higher temperatures. Pronounced step-bunching coincided with large ( 4 × 2 ) domains at the step-edges, causing smoother steps for the [11̅0] misorientation. This Ga-rich reconstruction at the step-edges is needed for the Schwoebel barrier to induce step-bunching. At higher temperatures of ( 2 × 4 ) domains grow in size, the Schwoebel barrier reduces and nucleation becomes easier on this surface which reduces diffusion length and thus step-bunching.